Innovation networks: the effects of collaboration in the oil and gas industries. (2017) - Barboza, Adonis Pedro Coutinho; Laruccia, Mauro Maia
This qualitative study of the innovation performance aims to determine whether collaboration affects patent productivity given network metrics such as centrality, structural holes, and hierarchy. The sample used in this study consists of 1, 811 patents and 3, 213 researchers related to the C10 area of knowledge with regard to oil, fuel gases, and lubricants. The study shows that Sinopec Limited has higher patent productivity than Royal Dutch Shell plc, BP plc, and Total S.A., with a descriptive level p-value of less than 0.05 and a 95% confidence interval. In contrast, BP, Shell, and Total cannot be differentiated based on patent productivity. The regression models in this study provided an explanatory power of 59.03% for Total, 42.43% for BP, 39.10% for Sinopec, and 14.14% for Shell. Although these models are limited to those specific companies, their statistically significant results explain patent productivity, confirming the hypotheses and providing a basis for future research.